Emerging Diagnostic Tools to Decide When to Discontinue Nucleos(t)ide Analogues in Chronic Hepatitis B - Margarita Papatheodoridi; George Papatheodoridis (Cells, 2020)
The aim of this review is to outline emerging biomarkers that can serve as diagnostic tools to identify non-cirrhotic chronic hepatitis B (CHB) patients who could safely discontinue nucleos(t)ide analogues (NAs) before HBsAg loss. Regarding possible predictors of post-NAs outcomes, a number of studies have evaluated numerous factors, which can be categorised in markers of hepatitis B virus (HBV) activity, markers of host immune response and markers of other patient characteristics. In clinical practice, the most important question for patients who discontinue NAs is to differentiate those who will benefit by achieving HBsAg loss or at least by remaining in remission and those who will relapse requiring retreatment. Most of the discontinuation studies so far came from Asian and only few from European populations and examined the rates and predictors of post-NA virological and/or combined relapses or HBsAg loss. To date, there is still controversy about predictors of post-NA relapses, while only HBsAg serum levels at NA discontinuation seem to be the most robust predictive marker of the probability of subsequent off-treatment HBsAg seroclearance. Newer viral markers such as HBV RNA and hepatitis B core-related antigen seem promising, but further research is required.